Marx's Value, Exchange and Surplus Value Theory: A Suggested Interpretation - Jean Cartelier (Levy Economics Institute of Bard College, 1989)
The concept of commodity society based on a specific division of labour (opposition between private and social labor) and that of surplus-value are the most prominent achievements of Marx's intellectual efforts in dealing with the economy of capitalism. This paper attempts to evaluate the consistency of the theoretical propositions inherent in these concepts. The main contention is that an internal criticism of Marx's theory of exchange and surplus-value leads one to restate it in a different framework. This framework. Which may be called monetary approach represents an alternative to value theory. The first section of the paper is devoted to Marx's value theory, especially to the form of value analysis. We suggest that Marx did not succeed in deriving money from commodity. As a consequence, money, if any, has to be presupposed at the same time as the specific division of labor. Doing so is breaking with the typical abstraction of value theory which substitutes values for monetary magnitudes, the former being thought of as expressing the essence of society in contrast with the latter conceived as surface phenomena. The second section points out the logical inconsistencies which make the surplus value theory unsuitable for its purpose. A restatement will be suggested in which the monetary character of economic relations is again central.
Keywords: 330